2012
DOI: 10.1007/s10567-011-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Family Factors in the Development, Treatment, and Prevention of Childhood Anxiety Disorders

Abstract: It is now widely accepted that anxiety disorders run in families, and current etiological models have proposed both genetic and environmental pathways to anxiety development. In this paper, the familial role in the development, treatment, and prevention of anxiety disorders in children is reviewed. We focus on three anxiety disorders in youth, namely, generalized, separation, and social anxiety as they often co-occur both at the symptom and disorder level and respond to similar treatments. We begin by presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 192 publications
(227 reference statements)
1
89
1
3
Order By: Relevance
“…Much of this work has focused on identifying the processes and conditions through which different parenting styles are linked with anxiety and depression. Parenting styles represent broad tendencies that are typically stratified or categorized across different dimensions of control versus autonomy, warmth versus rejection, or demandingness and responsiveness (Drake and Ginsburg 2012;Rohner et al 2005). Parenting styles are thought to play an important role in the development of important skills and competencies necessary for healthy emotional adjustment and wellbeing throughout one's life (e.g., Chang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this work has focused on identifying the processes and conditions through which different parenting styles are linked with anxiety and depression. Parenting styles represent broad tendencies that are typically stratified or categorized across different dimensions of control versus autonomy, warmth versus rejection, or demandingness and responsiveness (Drake and Ginsburg 2012;Rohner et al 2005). Parenting styles are thought to play an important role in the development of important skills and competencies necessary for healthy emotional adjustment and wellbeing throughout one's life (e.g., Chang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Beside the lack of consistent evidence of the added value of involving parents, it is also rarely investigated whether involving parents actually improves their parenting with regard to anxiety enhancing parenting and whether involving the family improves family functioning (Breinholst et al 2012;Drake and Ginsburg 2012;Ginsburg et al 2004), or does so to a larger extent than when treating the child alone. That is, it might be that when a child is successfully treated with CCBT, parental overprotection will decrease as a result.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that some parental punitive reactions in response to anxious children's signs of distress may inadvertently ''force'' approach to feared situations (e.g., ''you are going the birthday party, or you will not play videogames tomorrow'') among children with high levels of interpretation biases. At the same time, prior studies have shown that parents of children with (vs. without) clinical anxiety display greater over-involvement and overprotective behaviors (as opposed to punitive responses), and that such reactions contribute to elevated anxiety (Drake and Ginsburg 2012). Given that moderator findings with the punitive subscale of the CCNES were specific to mother reports of child anxiety, it is also possible that high-punitive mothers may simply underreport their children's true levels of anxiety, as they are by definition more likely to disapprove of such symptoms.…”
Section: Discussionmentioning
confidence: 98%